Patterns of care of breast cancer patients in Morocco – A study of variations in patient profile, tumour characteristics and standard of care over a decade. (October 2021) - Mrabti, Hind; Sauvaget, Catherine; Benider, Abdellatif; Bendahhou, Karima; Selmouni, Farida; Muwonge, Richard; Alaoui, Leila; Lucas, Eric; Chami, Youssef; Villain, Patricia; Abousselham, Loubna; Carvalho, Andre L.; et al.
Abstract: Guided by a national cancer plan (2010–19), Morocco made significant investments in improving breast cancer detection and treatment. A breast cancer pattern-of-care study was conducted to document the socio-demographic profiles of patients and tumour characteristics, measure delays in care, and assess the status of dissemination and impact of state-of-the-art management. The retrospective study conducted among 2120 breast cancer patients registered during 2008–17 at the two premier-most oncology centres (Centre Mohammed VI or CM-VI and Institut National d'Oncologie or INO) also measured temporal trends of the different variables. Median age (49 years) and other socio-demographic characteristics of the patients remained constant over time. A significant improvement in coverage of the state-financed health insurance scheme for indigent populations was observed over time. Median interval between onset of symptoms and first medical consultation was 6 months with a significant reduction over time. Information on staging and molecular profile were available for more than 90% and 80% of the patients respectively. Approximately 55% of the patients presented at stage I/II and proportion of triple-negative cancers was 16%; neither showing any appreciable temporal variation. Treatment information was available for more than 90% of the patients; 69% received surgery with chemotherapy and/or radiation. Treatment was tailored to stage and molecular profiles, though breast conservation therapy was offered to less than one-fifth. When compared using the EUSOMA quality indicators for breast cancer management, INO performed better than CM-VI. This was reflected in nearly 25% difference in 5-year disease-free survival for early-stage cancers between the centres. Highlights: Morocco achieved significant progress in quality of breast cancer care in last decade. Access delay reduced significantly over time but was still high at median 6 months. More than 80% breast cancer patients had complete molecular profiles. Many gaps still exist in quality of treatment; <20% eligible patients receive BCT. Difference in quality resulted in 25% difference in 5-year survival for stage I/II.